Exploring the agroforestry adoption gap: financial and socioeconomics of litchi-based agroforestry by smallholders in Rajshahi (Bangladesh) - Rahman, S.A.; Groot, W.T. de; Snelder, D.J. (Springer, 2008)
This paper takes a multistrata agroforestry system, based on Litchi chinensis and widely practised in North Bangladesh, as a case study to address the common problem of lack of adoption in agroforestry. Although the financial cost-benefit analysis of agroforestry systems may show clear-cut profitability, these systems are often hardly adopted by farmers. Our data clearly show this pattern. Net present values and returns to labor of agroforestry were five times higher than those of alternative (annual) crops, and yet the adoption rate remained very low, even though an agroforestry project had been carried out in the study area and agroforestry had positive cultural value. Common economic reasoning is that in such cases, adoption is hampered by capacity constraints of the farmers. Our data allow to argue, however, that not the capacities but rather the motivations of the farmers are key, in spite of the financial characteristics of the system. This is caused by the underlying institutional structures, that are highly unconducive to agroforestry. We conclude that action for agroforestry should focus first of all to get supportive institutions (rules and organisations) in place before focusing on trees and projects, if needed at all.